POLYCROPS: Successful associative crops in three municipalities of Boyacá - Bautista González, Harold Ignacio; Castellanos González, Leónides; Montañez Acevedo, Gladys (Sello Editorial Unipamplona, 2025)
The research project “Implementation of associative agricultural models with traditional polycultures for economic and environmental management in the department of Boyacá” was aimed at the development of cultural and agronomic practices based on the association of transitory species, benefiting 12 producer families with an agricultural vocation in 12 municipalities, through field pilot tests which were based on the creation and design of associative models that promoted agricultural production under environmentally sustainable parameters. The objective of this publication is to publicize the result of the technical, economic and social validation of nine associative models in the municipalities: Soatá, Belén and Panqueba. The research was carried out applying a qualitative and quantitative experimental methodology, with a completely randomized design in two factors: the first factor corresponds to polyculture with three levels (three types of associative models in each municipality) and the second factor that concerns the monoculture plot (control), with four farms for each model that were the repetitions; for a total of 12 farms per municipality.